New synonymy for a species of mealybug in the genus Pseudococcus (Hemiptera: Pseudococcidae) that occurs on fruit trees in Chile - González, Roberto H.; Prado, Ernesto (Zootaxa, 2012)
In July of 2011, we each became aware that we were studying the same Chilean mealybug species. The research by González (2011) emphasized the biology, economic importance, and control of the species on fruit, and described it as the new species Pseudococcus rubigena González. The research by Prado in Correa et al. (2011) provided a detailed description using molecular and morphological data and described the new species as P. meridionalis Prado. Based on the Principle of Priority (Article 23) in the International Code of Zoological Nomenclature (1999), one of these names must have precedence. Unfortunately, both papers were published at approximately the same time. The date of publication of the Correa et al. paper is clearly marked as June 22, 2011. The exact date of publication of the González book was not clear because it did not give a specific date, only 2011. To establish the exact date, a certificate of publication was requested from the publisher (Imprenta Italiana Ltda.) by González. In a letter dated November 23, 2011, Nelson Cannoni M., Gerente General, Impreta Italiana indicated “ULTIMO DESPACHO DE EJEMPLARES: 30 de junio de 2011.” This is considered the date of publication for the name P. rubigena which was predated by P. meridionalis by just nine days. Therefore the following synonymy is proposed.